Nonexistence of solutions for singular nonlinear ordinary inequalities - Xiaohong Li (Electronic Journal of Qualitative Theory of Differential Equations, 2015)
In this paper we prove nonexistence theorems of nonnegative nontrivial solutions for a singular nonlinear ordinary inequality in bounded domains with singular points on the boundary. The proofs are based on the test function method developed by Mitidieri and Pohozaev. We also give the examples demonstrating that the conditions obtained are sharp in the case of the problem under consideration